Science and Religion: Moving Beyond the Credibility Strategy - Lorrimar, Victoria (Zygon, 2020)
Reeves condemns the recruitment of scientific methods by representative theologians to lend credibility to their theological claims. His treatment of Nancey Murphy's use of Lakatosian research programme methodology is focused on here, and his proposal that science and religion scholars might act as “historians of the present” to advance the field is explored. The “credibility strategy” is set in historical context with an exploration of some of the science and religion field's original commitments and goals, particularly in terms of the emphasis on rationalism and corresponding neglect of the imagination, and the value of more creative input in promoting better dialogue between science and religion is highlighted.